Psychological adjustment of teenagers in school (Revista Estudios Psicológicos, 2022)
The main objective of this study was to evaluate psychological adjustment based on the internalized and externalized behavior of adolescents in seventh and eleventh grades. It was carried out under a positivist paradigm methodology, with a quantitative approach, descriptive cross-sectional type, in which the Youth Self-Report of Achenbach and Rescolar was used to obtain information on psychological problems in adolescents. A total of 142 students (57% female and 43% male) between 12 and 18 years of age from an educational institution participated. The data were analyzed through descriptive statistics using the SPSS program. As main results, normal ranges were found at the level of psychological adjustment, internalized and externalized behavior in the adolescents evaluated.
Keywords: psychological adjustment; adolescents; internalizing and externalizing behaviors